FORMATION OF PERSONAL QUALITIES STUDENTS BY WORKING ON PROJECTS LIKE PROBLEM OF ACMEOLOGY - Dimitrova, Neli (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Modern way of life requires a change in the educational system. This calls for new approaches to education. For this purpose there should be well prepared and highly qualified teachers. Need usavarshentsvane the professional activity of teachers requires a change in the training of teaching staff in the university. Razi solving task requires a new structural approach to quality educational training of young specialists. The purpose of this research is to form personal qualities that enhance the professionalism of the students - future teachers of technology education by working on projects like problem of akmeology.